Musiques et musiciens à Paris dans les années trente - Pistone, Danièle (Paris Champion, 2000)
This collective volume, the work of around forty specialists, is a vast new synthesis of the state of Parisian music in the 1930s: from political considerations to the evolution of lyric theatres, via the repertoire of symphony orchestras and chamber music societies, not forgetting chanson and jazz. From neoclassicism to modernity, from the rise of mass culture to the affirmation of ‘musical ethnology’, it sets out to show how, through its new development conditions (radio, records, cinema, etc.), music remained in harmony with this era, reflecting its growing eclecticism and swirling abundance, but also the atmosphere of crisis and its disastrous fate. (Translated with DeepL.com)
Includes bibliographical references (p. 557-573) and index.
Keywords: 20th Century (1901-2000); Music history -- History and criticism; Music criticism; Musician; Paris (France)